2005
DOI: 10.1038/nchembio755
|View full text |Cite
|
Sign up to set email alerts
|

Actin microfilament aggregation induced by withaferin A is mediated by annexin II

Abstract: The actin cytoskeleton supports diverse cellular processes such as endocytosis, oriented growth, adhesion and migration. The dynamic nature of the cytoskeleton, however, has made it difficult to define the roles of the many accessory molecules that modulate actin organization, especially the multifunctional adapter protein annexin II. We now report that the compound withaferin A (1) can alter cytoskeletal architecture in a previously unknown manner by covalently binding annexin II and stimulating its basal F-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 21 publications
2
115
0
3
Order By: Relevance
“…[29][30][31][32] WFA binds covalently to annexin II and stimulates its basal F-actin cross-linking activity 29 ; however, at the low nanomolar concentrations, we did not observe significant actin defects (Fig. 2a).…”
Section: Cancer Therapymentioning
confidence: 67%
See 2 more Smart Citations
“…[29][30][31][32] WFA binds covalently to annexin II and stimulates its basal F-actin cross-linking activity 29 ; however, at the low nanomolar concentrations, we did not observe significant actin defects (Fig. 2a).…”
Section: Cancer Therapymentioning
confidence: 67%
“…every other day 1 week after implantation of 4T1 cells. A dose range beginning with 0.1 mg/kg up to 4 mg/kg was selected based upon the PK analysis above and a previous report (29). The average body weight of control and WFA-treated mice did not differ significantly throughout the study (data not shown).…”
Section: Wfa Inhibits In Vivo Breast Cancer Metastasis and Induces VImentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, while there has been a range of studies of individual annexin expression in specific types of primary tumours, there have been no significant previous studies of annexin expression in metastasis. In addition, more recently individual annexins have been proposed as putative tumour biomarkers and potential therapeutic targets in cancer (Oh et al, 2004;Falsey et al, 2006;Wozny et al, 2007). The expression and cellular localisation of annexins have received very little previous study in colorectal cancer, with only annexin A2 having been investigated (Emoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Withaferin A can alter cytoskeletal architecture by covalently binding annexin II and stimulating its basal F-actin crosslinking activity. 20 Leishmania, a unicellular kinetoplastid protozoan parasite, is the causative agent of leishmaniasis. With the spread of human immunodeficiency virus (HIV), the parasites pose a much greater threat than before.…”
mentioning
confidence: 99%